Pre- and Probiotics to Increase the Immune Power of Colostrum in Dogs - Alonge, Salvatore; Aiudi, Giulio Guido; Lacalandra, Giovanni Michele; Leoci, Raffaella; Melandri, Monica (Frontiers in Veterinary Science, 2020)
Wide differences in Ig concentration in canine colostrum have been reported. Thus, some litters can be at risk of passive immune transfer failure. Present study evaluated if supplementation with MOS, FOS, E. faecium and L. acidophilus along pregnancy increases colostrum quality. Twenty Great Dane bitches were divided into 4 groups. Control group (CG) received standard diet, only. Diet was supplemented with pre- and probiotics in other 3 study groups during: the last (1WG), last 2 (2WG) and last 4 (4WG) weeks of pregnancy, until parturition. Serum samples were collected at estrous (T0), supplementation beginning (T1) and parturition (T2). Colostrum was collected at C-section end. The IgG, IgM, and IgA were assayed on both matrices. In serum, IgG were higher at T0 than at parturition in all study groups and they significantly lowered from T0 to T1 in all groups. In colostrum, IgG and IgM were significantly higher in 4WG, while IgA already increased in 2WG group. Four-week pre- and probiotic supplementation resulted in the best immune properties of colostrum, as by the higher IgG, IgM and IgA colostrum levels found in 4WG. Further studies would verify the exact mechanisms involved: pre-partum IgG mammary accumulation and B-cells GALT proliferation and mammary transfer. Further trials would verify whether these beneficial effects of pre- and probiotics on colostrum also lead to improved clinical conditions and immunological functions of newborns and puppies.